Determinants of internal corporate social responsibility practices and employee engagement: a study of Malaysian private higher education institution - Chan, Tak Jie; Hossen, Md. Monir; Mohd Hasan, Nurul 'Ain (Human Resource Management Academic Research Society, 2020)
Corporate Social Responsibility (CSR) has emerged tremendously as an important field of study. However, the influence of internal corporate social responsibility (ICSR) practices in education industry remain understudied. The purpose of this study was to investigate the relationship between ICSR practices and employee engagement in a private university in Malaysia. A quantitative (survey) method was employed using purposive sampling in which 93 valid responses were generated. The data were then analyzed using Pearson-Product Moment Correlation and Multiple Regression test through the Statistical Package for the Social Sciences (SPSS) version 25.0. Based on the findings, ICSR dimensions, namely training & education and working environment yielded positive and moderate relationships with employee engagement, whereas employment stability and employee empowerment generate positive and high relationships with employee engagement. In addition, multiple regression analysis showed that employment stability and training & education were the significant two predictors that can help to increase the employee engagement. Conclusion, implications, and suggestions for future studies are also discussed.